THE SIGN OF HISTORICIST ARCHITECTURE IN 21th CENTURY TURKEY: MAIN UNIVERSITY GATES - ONUR IŞIKOĞLU, Beyza; ÖZEREN, Ömer (EUROASIA JOURNAL OF SOCIAL SCIENCES & HUMANITIES, 2020)
Although architecture is simply related to the practice of producing built environments, it also has a political character that shapes the social structure. In this respect, architecture is a structure that makes ideologies visible and concrete. Architecture is a powerful tool and representation in the process of creating an idealized society. In this context, recent architectural environment in Turkey, giving reference to historical items and historical style has been an attempt to revive the scene. Such an architectural environment must be discussed not only in terms of architectural form and style production, but also in the triangle of ideology-political power-architecture. In this debate, the subject of the study as the first, with power routing in Turkey has created a character with historical items and conservative fore historicist architecture. Signs of historicist architecture in Turkey showing the effect of public and educational buildings input in an identity that qualification for those working in university education structures was examined under the main university gates. When the main university Gates examination examples in Turkey, for example, that fed many of the same conservative ideology and was observed to exhibit a homogeneous appearance. This attitude, which idealizes historicism, raised the problem of similarity in universities that have a strong representation feature for our cities and prevented important science production areas such as universities from having a unique identity. Finally, as in public buildings in Turkey that it also includes the main university gates that have "neo" the stylistic, ideological-based is considered to be part of a new initiative historiography.